2009
DOI: 10.1111/j.1537-2995.2008.01974.x
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Plasmodium falciparum–infected red blood cells from whole blood by leukoreduction filters

Abstract: PS expression by RBCs leads to their adherence within leukoreduction filters. Malaria-infected RBCs are retained via more than one mechanism. The efficiency of removal requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…after the study period) may also have contributed to a further reduction in the TTM residual risk. In a recent study, Cardo et al [23] demonstrate the removal of P. falciparum infected red blood cells from whole blood by leucodepletion filters. The authors speculate that this phenomenon might partially explain the observed decrease in incidence of TTM in the USA, which has paralleled the increasing use of leucodepletion [10,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…after the study period) may also have contributed to a further reduction in the TTM residual risk. In a recent study, Cardo et al [23] demonstrate the removal of P. falciparum infected red blood cells from whole blood by leucodepletion filters. The authors speculate that this phenomenon might partially explain the observed decrease in incidence of TTM in the USA, which has paralleled the increasing use of leucodepletion [10,23].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Cardo et al [23] demonstrate the removal of P. falciparum infected red blood cells from whole blood by leucodepletion filters. The authors speculate that this phenomenon might partially explain the observed decrease in incidence of TTM in the USA, which has paralleled the increasing use of leucodepletion [10,23]. However, despite the implementation of leucodepletion in France and the UK since the mid‐1990s, a similar decline in TTM incidence is not immediately evident [3,5].…”
Section: Discussionmentioning
confidence: 99%
“…The new NWF filter could be used for purification of P. falciparum samples too. In this study, including mature stage P. falciparum -infected RBC could pass through the non-woven fabric filter material, this result is different from the report of using routine transfusion filter to deplete P. falciparum- infected RBC [22], this may be caused by the difference of filtration materials, sample size and iRBC load.…”
Section: Discussionmentioning
confidence: 59%
“…We have also shown that RBC and WB leucoreduction by filtration reduces T. cruzi concentrations by 99% and consequently can potentially decrease Chagas disease transfusion-transmission risk [2,3]. Moreover, Cardo et al [4] have reported the adherence of malaria-infected RBC to WB filters by at least three different mechanisms, suggesting that the unexplained decline in the incidence of transfusion-transmitted malaria in the last decades could be due to the increasing use of leucoreduction filters. The effectiveness of leucoreduction against other parasites, such as Babesia sp., remains to be demonstrated.…”
Section: Dear Editormentioning
confidence: 53%